2001
DOI: 10.1902/jop.2001.72.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable Materials for Guided Bone Regeneration Prior to Implant Placement and 7‐Year Follow‐Up: Report of 14 Cases

Abstract: These results confirm the possibility of regenerating bone by means of bioabsorbable materials, assuring at the same time the long-term success for implants inserted in regenerated sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 20 publications
3
59
0
4
Order By: Relevance
“…Surgical procedure Five studies (10,12,(14)(15)(16)) used a combination of autograft with xenograft, hydroxyapatite or homologous bone. In the remaining 8 studies a single type of graft was used: autologous bone (8,10,13,14), homologous bone (11,14), bovine bone (10,18,19) or hydroxyapatite (17). In two studies (13,15) the intraoral autologous grafts were obtained from the retromolar region, while in one publication the graft was harvested from the mandibular ramus (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical procedure Five studies (10,12,(14)(15)(16)) used a combination of autograft with xenograft, hydroxyapatite or homologous bone. In the remaining 8 studies a single type of graft was used: autologous bone (8,10,13,14), homologous bone (11,14), bovine bone (10,18,19) or hydroxyapatite (17). In two studies (13,15) the intraoral autologous grafts were obtained from the retromolar region, while in one publication the graft was harvested from the mandibular ramus (16).…”
Section: Resultsmentioning
confidence: 99%
“…In the studies involving dehiscences or fenestrations (8,10,14), the particulate grafts were placed with the implants in the same surgical step. In 5 studies (12,13,15,17,18) biopsies were obtained of the implant receptor bone at the end of the graft healing period, and the histological study confirmed an adequate bone structure for implant placement. The implants are to be placed once primary stability has been assured.…”
Section: Healing Timementioning
confidence: 96%
“…Older investigations described a resorption rate of 5 to 15% per year after orthopedic application [101]. Degradation of sHA is hard to control and predict due to a great number of influencing factors and individual variations among patients [102].…”
Section: Degradationmentioning
confidence: 99%
“…Некоторые авторы указывают, что эффективность НТР варьирует в пределах 85-98,3% [6,21,24,25,35,51]. Основные недостатки данной методики: регенированная костная ткань структурно отличается от естественной; возможно обнажение мембраны, что ставит под сомнение успешный исход вмешательства; относительно длитель-ный срок лечения [50].…”
Section: стоматология 2 2015unclassified